Effects of xylanase and cellulase supplementation on early growing stage, caecal bacteria population and fermentation profiles of broiler fed with palm kernel meal - Ahmad, Sharmila (2014)
The optimum inclusion of palm kernel meal in broiler diets is reported about 20% without having any detrimental effect on the performance and health of broilers. The addition of enzyme in palm kernel mealdiet for broilers isnecessary in promoting growth performances of the broilers through increase in feed efficiency and digestibility. Since, previous study only focusing on their effect on growth performance; therefore, the present study was conducted to study the effect of enzyme supplementation in palm kernel mealdiet on caecal fermentation profiles, early growth performances and caecal bacteria population of broilers. The in-vitro analysis was carried out by incubating the formulated diets with caecal digesta of broilers for 72 hours at 39±5oC. The gas production and end products of the fermentation were examined. The gas production rate of unsupplemented and enzyme-supplemented palm kernel meal diet observed was similar in trends. However, it was found that the amount of acetate was significantly (P<0.05) reduced with enzyme supplementation, whilst the in-vitro dry matter degradability of both, starter and finisher diet were improved (P<0.05), with more outstanding result observedfollowing xylanase supplementation at 11.09 and 17.59%, respectively.In the feeding trial, 75 broiler chicks were randomly allocated to three dietary treatment groups receiving diet containing 20% of palm kernel meal with or without xylanase and cellulase supplementation. The individual body weight and feed intakewere recorded weekly, and at day 35, broilers were slaughtered for ceacal digesta collection. Both enzyme addition did not improve the average daily gain of broiler at starter phase (1- 21 days), but had improved at grower phase (22-35 days), where broilers fed with xylanase supplementation had improved their body weight by 7% compared to control diet (61.98 g/bird). The similar result was also observed in the final body weight of broilers, where xylanase-supplemented group was the highest followed by control and cellulase-supplemented group which values is 1495.2, 1436.8 and 1367.8 kg, respectively. In the enumeration of caecal bacteria population, lactic acid bacteria and Salmonella spp. population were reduced, by 4.1 and 1.9% in xylanase supplemented group, and 8.3 and 7.9%in cellulase supplemented group, respectively. In contrast, the caecal bacteria population quantified using real-time PCR analysis revealed that enzyme supplementation had reduced the number of total bacteria, lactic acid bacteria, enterococcus, enterobacteria, Escherichia coli, bifidobacteria and Salmonellaspp., respectively compared to unsupplemented palm kernel meal diet. Apart from that, significant negative correlation (P<0.01) was observed between the population of coliform bacteria (-0.97) and Salmonella spp. (- 0.84) with n-butyrate in caecal digesta of broilers. The current data show that nbutyrate have a toxic effect on coliform bacteria and Salmonella spp. In conclusion, enzyme supplementation in 20% palm kernel meal diet was only effective in improving the body weight of broilers at growing phase but not in the starter phase. So, reducing the amount of palm kernel meal in the starter broiler diet is recommended; since, body weight of broilers fed 20% palm kernel meal diet was not improved, even with enzyme addition.